Impact of plant pathogens on potato rhizosphere enzymes and microbial dynamics - Xu, Gaihuan; Deng, Linmei; Dao, Jian; Wang, Wenping; Liu, Chunjiang; Yang, Yanli; Zhao, Jing; Liu, Xia (Frontiers in Plant Science, 2025)
Soilborne pathogens significantly impact potato productivity by altering rhizosphere enzymatic activities and microbial communities. Pathogen-induced changes in enzyme activities are correlated with shifts in microbial community composition, but causal relationships remain unclear. This study investigates the effects of five key pathogens—Phytophthora infestans, Streptomyces scabies, Spongospora subterranea, Ralstonia solanacearum and Globodera rostochiensis—on soil enzyme activities and microbial community structure in potato rhizosphere soils under continuous cropping. This experiment involved pathogen inoculation and soil sampling in potato rhizosphere soils, with treatments replicated three times. Potatoes were planted on March 22, 2023, and harvested on August 25, 2023. Enzymatic activities were measured at different growth stages, and microbial communities were analyzed using high-throughput sequencing. Pathogen-induced variations in enzymatic activities were observed, potentially promoting disease proliferation. For instance, under S. scabies stress, urease (URE) activity increased significantly at the full flowering and post-flowering stages, while catalase (CAT) activity decreased significantly during the seedling and full flowering stages. Under S. subterranea stress, activities of urease, sucrase (SUC), and alkaline phosphatase (ALP) decreased. M. nematode stress led to a decline in URE and sucrase activities. P. infestans infection led to a decrease in URE activity at the sowing stage. Furthermore, microbial community composition was significantly correlated with disease incidence, with specific taxa such as Planctomycetes and Basidiomycota showing negative correlations with S. subterranea incidence, while Candidatus Dormibacteraeota and Ascomycota were positively associated with P. infestans. These results suggest that pathogen-induced changes in enzymatic activities play a critical role in disease dynamics and microbial interactions. The findings highlight the importance of understanding the effects of soilborne pathogens on soil enzyme activities and microbial communities, providing insights into disease management strategies in potato farming.